Forestation in Hypergraphs: Linear k-Trees - Parekh, Ojas (The Electronic Journal of Combinatorics, 2003)
We present a new proof of a result of Lovász on the maximum number of edges in a k-forest. We also apply a construction used in our proof to generalize the notions of a k-hypertree and k-forest to a class which extends some properties of trees, to which both specialize when k=2.